Chapter 4 Decisions on saving and investment in the digital era - Kubinska, Elzbieta; Adamczyk-Kowalczuk, Magdalena; Macko, Anna (Taylor & Francis, 2023)
The chapter presents the results of undertaken primary research, which delves into the relationship between economic and psychological factors in the realm of digital finance. The research examines the behavior and preferences of market participants and their relationship with financial literacy. It explores various dimensions such as saving propensity, investment diversification, portfolio selection, profit-risk relationship, typology of financial literacy, self-assessed financial knowledge, post-pandemic changes in trust in different forms of payment, usage of digital payment methods, familiarity with robo-advisory, preferences for AI advisory in different spheres, and preferences for saving and investment robo-advisory recommendations. The research was conducted among an internationally diverse sample from Poland, India and the USA, and took place in the post-pandemic reality. Comparing data from international samples, research conducted for this book shows the current picture of financialization within three contemporary, but culturally and economically diversified societies. The empirical chapter includes models that demonstrate the relationships between economic and psychological variables, as well as characteristics related to decision-making in the digital reality. These models allow for generalization of the research to a wider groups, of international financial markets participants